can you add anything to both sides of an equation and have it be valid?

ssncrockett

New member
Joined
Nov 2, 2011
Messages
1
Here is the problem--The logic seems valid until you reach the end where 2=1????


Let’s start with two variables, x and y.

Let x = y (this is our starting equation).

Multiply both sides by x (OK because we don’t violate the equal sign – we’re ‘balancing’ our work across that sign). We get x² = xy.

Subtract y² from both sides (again OK because we don’t violate the equal sign).
We get x² – y² = xy – y².

Factor the left side. x² – y² = (x +y)(x – y).

Factor the right side. xy – y² = y(x – y).

Set these two factors equal to each other. They started that way, so there’s no problem here.

We get (x + y)(x – y) = y(x – y).

Now, since there's the same (x – y) factor on both sides of the equal sign, we can cancel them out..

We’re left with x + y = y.

But, we originally set x = y. Therefore, let’s replace x with y on the left side of the equation.

We get y + y = y. or 2y = y.

Now, the last step. We divide both sides by y. The result is 2 = 1!

OK, we know that if this proof is correct, then all of our math is entirely wrong.
After all, if 1 = 2, then 2 = 3, etc. But what’s the deal? Where did we go wrong?

That’s for you to figure out.
 
Top